KINABALU NATIONAL PARK, UNESCO WORLD HERITAGE SITE: ASSESSMENT OF ENVIRONMENTAL ISSUES, TOURIST SATISFACTION AND PARK MANAGEMENT - Abdul Latip, Normah; Karim, Rehmat; Jaafar, Mastura; Marzuki, Azizan; Ahmad, A. Ghafar; Syed Abdullah, Sharifah Zahhura; Omar@Umar, Mohd Umzarulazijo (PLANNING MALAYSIA, 2021)
National parks serve as rural ecotourism attractions, the management of which must strike a balance between economic productivity and the protection of the park’s natural value. Faced with the increased pressure of rising visitor numbers park management must give greater consideration to the tourist experience and tourist satisfaction. This paper examines the relationship between park management, tourist satisfaction, and environmental issues. Moreover, this paper considers the mediating role of environmental issues on the relationship between park management and tourist satisfaction. A questionnaire survey was administered to visitors of Malaysia’s Kinabalu National Park. In total, 351 completed questionnaires were returned and Partial Least Squares-Structural Equation Modelling (PLS-SEM) was used to analyze the resultant data using SmartPLS 2.0. The results showed that park management has a strong effect on tourist satisfaction and environmental issues. The results also revealed that environmental issues play a mediating role in the relationship between park management and tourist satisfaction.